Investigating technology integration readiness of English first additional language educators: a case of South African rural public schools - Lediga, Mamaroba Sylvia (My University, 2023)
Technology use is gaining momentum the world over, including South Africa. Therefore, technology use presupposes technology integration, and educators appear better positioned to ensure its integration. As a result, the integration of technology by English First Additional Language (EFAL) educators is of significant importance to learners’ academic development. The purpose of this research study was to investigate South African rural public schools EFAL educators’ readiness to integrate technology into EFAL content. The study was underpinned by a combination of two theoretical frameworks, the Technology Readiness Index (TRI) and the Technological Pedagogical Content Knowledge (TPACK). The study followed a quali-quantitative approach and an exploratory research design. The triangulation data collection method employed questionnaires, interviews and equipment checklists. Findings indicated that EFAL educators in rural public schools are not ready to embrace the Fourth Industrial Revolution (4IR) and lack relevant and adequate infrastructure to integrate technology. Findings further revealed that EFAL educators need proper training in technology skills and technical support in order to be ready to integrate technology into EFAL. Pertinent intervention strategies should include the collaboration of all stakeholders to improve the Information Communication Technology (ICT) context in rural public schools. Additionally, the Department of Basic Education (DBE) has to bridge the gap between rural and urban schools in SA by providing adequate technology support to rural public EFAL educators.
Thesis (Ph.D. (English Studies)) -- University of Limpopo, 2023
Keywords: Technology integration; EFAL; Rural public schools; Technology readiness; Educational technology; Public schools-- South Africa; Technology -- Study and teaching (Secondary) -- South Africa